Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2019
DOI: 10.1209/0295-5075/126/64001
|View full text |Cite
|
Sign up to set email alerts
|

Acoustic emission from successive impacts on elastic membranes: The physics of the screaming balloon

Abstract: When a hex nut or a ridged-edge coin, placed inside an inflated rubber balloon and spun vigorously, it emits a surprisingly loud and clear sound as the spinning object impacts the rubber and triggers vibrations of the membrane, a phenomenon known as the screaming balloon. We identify the mechanisms behind the acoustic emission and show that the fundamental frequency of the sound is given solely by the rate of successive impacts of the spinning object onto the membrane as it rolls without slipping. A counter-in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 27 publications
(28 reference statements)
0
1
0
Order By: Relevance
“…Literature that was concerned about higher crack rates and degrees of crack plasticity suggested that the extent of crack tip plasticity becomes indispensable where an increase in the size of the plastic zone occurs [31][32][33] as in low-cycle fatigue or with semi-ductile substrates. Hence, impact could be a significant damage source in different mechanical processes, and AE monitoring for such damage potential is crucial for the safety and establishment of structural systems [34][35][36][37]. Prosser et al [38] studied the released AE occurred by an impact of two projectile types on an aluminum and graphite/epoxy composites plate.…”
Section: Introductionmentioning
confidence: 99%
“…Literature that was concerned about higher crack rates and degrees of crack plasticity suggested that the extent of crack tip plasticity becomes indispensable where an increase in the size of the plastic zone occurs [31][32][33] as in low-cycle fatigue or with semi-ductile substrates. Hence, impact could be a significant damage source in different mechanical processes, and AE monitoring for such damage potential is crucial for the safety and establishment of structural systems [34][35][36][37]. Prosser et al [38] studied the released AE occurred by an impact of two projectile types on an aluminum and graphite/epoxy composites plate.…”
Section: Introductionmentioning
confidence: 99%